2013
DOI: 10.3109/13697137.2013.808182
|View full text |Cite
|
Sign up to set email alerts
|

Impact of osteoporosis and bone fracture on health-related quality of life in postmenopausal women

Abstract: The HRQoL analysis results in this study demonstrated a loss of quality of life in postmenopausal women with osteoporosis and confirmed that this loss is greater in women with prior osteoporotic fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 24 publications
0
15
0
3
Order By: Relevance
“…Tal estudo observou ainda que as mulheres utilizando moduladores seletivos dos receptores de estrógeno, tipo de terapia medicamentosa para a osteoporose, apresentaram menor impacto da osteoporose na qualidade de vida, particularmente no domínio físico, avaliado pelo SF-12v2 Health Survey e no domínio sexualidade, avaliado a partir da Cervantes Scale. Esse dado confirma o achado da atual pesquisa, o que mostra a influência da osteoporose sobre a sexualidade feminina 28 .…”
Section: Discussionunclassified
“…Tal estudo observou ainda que as mulheres utilizando moduladores seletivos dos receptores de estrógeno, tipo de terapia medicamentosa para a osteoporose, apresentaram menor impacto da osteoporose na qualidade de vida, particularmente no domínio físico, avaliado pelo SF-12v2 Health Survey e no domínio sexualidade, avaliado a partir da Cervantes Scale. Esse dado confirma o achado da atual pesquisa, o que mostra a influência da osteoporose sobre a sexualidade feminina 28 .…”
Section: Discussionunclassified
“…Osteoporosis is responsible for fragility fractures, which are associated with decreased physical and social functions [8]. Because of high costs of their treatment, osteoporotic fractures constitute a serious problem, both for the public health and health care system.…”
Section: Introductionmentioning
confidence: 99%
“…The GINERISK study by Palacios et al with 4157 Spanish osteoporotic postmenopausal women showed a lower score in both the specific Cervantes Scale and the generic SF-12v2 Health Survey in those with osteoporosis. Interestingly, the HRQL loss was greater in women with prior osteoporosis fractures (Palacios et al, 2014). The Australian study AusICUROS applied the EQ-5D-3L questionnaire to both sexes adults over 50 years and described a low to moderate reduction in HRQL in subjects who suffered a low-impact fracture.…”
Section: Discussionmentioning
confidence: 99%
“…As the population ages, bone fractures also remain a significant health condition that impacts a high burden of the quality of life in obese subjects (Nielson et al, 2012, Compston et al, 2014, Palacios et al, 2014). The proportion of fractures occurring in obese people is significant, considering that clinical risk factors for fracture are similar in obese and non-obese subjects, although patterns of fracture and falling may diverge (Premaor et al, 2014).…”
Section: Introductionmentioning
confidence: 99%